Efficiency and Productivity Performance of Dompet Dhuafa based on the Type of Fund for 2010-2019 - Maliha, Hasna (SMART Insight, 2023)
The Islamic social finance industry in Indonesia is one of the industries that is growing very rapidly every year. This can be seen from the growth in the number of zakat management institutions that continue to increase, both those formed by the government and those formed by the community. The rapid development of the number of zakat management institutions raises the level of competition between zakat institutions getting stronger. To be able to compete in this industry, Dompet Dhuafa as one of the zakat management institutions must be able to compete with other zakat management institutions by improving performance optimally. The purpose of this study is to analyze the level of performance efficiency and productivity of Dompet Dhuafa for the 2010-2019 period based on the type of funds it manages. The methods used in this research are Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) methods. The estimation results show that Dompet Dhuafa has not achieved an optimal level of performance efficiency and relatively low productivity. This can be seen from the average efficiency score from 2010-2019 which only reached 0.66 and the average productivity level of Dompet Dhuafa reached 0.958.